STRUCTURE OF THE NODULAR GOITER IN CHILDREN - O. S. Rogova; L. N. Samsonovа; G. F. Okminyan (Бюллетень сибирской медицины)
For today the question of early diagnosis of nosological variants, the method of treatment and prevention of nodular goiter in children is still not fully resolved. There is a few available literature data about study of this problem in children. Objective: to study morphofunctional structure of thyroid nodules in children.The article provides information consisting of the results of a retrospective analysis of case histories of 73 patients, operated with nodular goiter in Z.A. Bashlyaeva Children’sCityClinicalHospital(Moscow) from 2003 to May 2015. The examination included an evaluation of the functional status of the pituitary-thyroid system: there were investigated serum thyroxine, triiodothyronine and thyroid stimulating hor-mone, also was performed thyroid scintigraphy 99mТc. In the postoperative period, there was carried out a final verification of the diagnosis according to the results of the histological conclusion. The histologi-cal type of nodal disease was defined by the WHO classification of 2004. It was established that in the structure of a single-node goiter in children prevail nodular colloid goiter with equal frequency in boys and girls, with the same frequency occurs thyroid adenoma, but more often in girls than in boys. The multinodular goiter equally often detected in girls and boys both nodular goiter colloidal with varying degree of proliferation and colloid in combination with follicular thyroid adenoma. "Hot" nodes in the multinodular goiter are more common than in the single-node goiter and more fre-quently in girls than in boys. The half of children with nodular pathology have "hot" nodes and one out of every three – decompensated form of functional autonomy. Decompensated form of functional autonomy of the thyroid gland in children with "hot" nodes detects regardless of the number of nodes. Papillary thyroid cancer occurs not only in patients with a single-node, but with a multinodular goiter. The results allow to draw conclusions about the heterogeneity of the morphological structure as a single-node and multinodular goiter in children, including papillary thyroid cancer.